A CORRELATIONAL STUDY BETWEEN HABIT IN LISTENING TO ENGLISH SONGS, VOCABULARY MASTERY, AND LISTENING SKILL - Despita Despita (STKIP PGRI Lubuklinggau, 2020)
The study is aimed to find out the correlation between habit in listening to English songs, vocabulary mastery, and listening skill of the tenth grade students of SMK KIMIA YTK Palembang. This study used a test and a questionnaire. The population of the study is all of the tenth grade students while the sample is 30 students taken by cluster random sampling technique. The techniques used to analyze the data are simple and multiple correlation and regression by using SPSS 17. The results of the study show that there is a positive correlation between habit in listening to English songs and vocabulary mastery toward listening skill, both partially and simultaneously. The positive correlation indicates that habit in listening to English songs and vocabulary mastery tend to go up or to go down together with the student’s listening skill. Keywords: correlation, habit, vocabulary mastery, listening skill